Spring seeds - Hokkanen, Mirka (New York, NY : Odd Dot, 2024)
Discover how seeds spring into action! As winter warms into spring, the amazing life cycle begins--seeds root and sprout and start to grow. From tiny carrot seeds to big avocado seeds and everything in between, discover what seeds can do in this pitch-perfect picture book for younger readers. With clear, informative text and bright, charming illustrations, as well as lots of hilarious interjections from the seeds themselves, this is an exciting start to a new nonficton picture book series exploring life cycles and the seasons.
Keywords: Seeds -- Juvenile literature; Spring -- Juvenile literature; Vegetables -- Juvenile literature; Fruit -- Juvenile literature; Gardening -- Juvenile literature; Creative nonfiction; Picture books